The Effect of Adding Molasses to Avocado Seed Flour (Persea americana) Silage on Physical and Chemical Quality - Yakin, Engkus Ainul; Mulyono, Ali Mursyid Wahyu; Purwati, Catur Suci; Sukaryani, Sri (Jurnal Biologi Tropis, 2026)
Avocado seed meal, a part of the avocado plant that is rich in antioxidants and various other nutrients and non-nutrient substances, has great potential to be used as an herbal additive in animal feed. This study aims to determine the effect of molasses addition on the nutrient profile and quality of avocado seed meal silage. The control treatment (P1) used plain avocado seed flour, while the experimental treatments (P2, P3, and P4) incorporated increasing molasses concentrations of 1%, 2%, and 3% of dry matter, respectively. All treatments were stored for 21 days at ambient temperature. The metrics assessed included nutrient composition, physical characteristics, and fresh silage quality. The data collected were evaluated using analysis of variance, and differences in parameter values among treatments were additionally examined with DMRT at a significance level of 5%. Findings showed that molasses notably improved the silage's nutrient composition and fresh quality (P<0.05), but had no significant effect on physical quality (P>0.05). The conclusion of this study suggests that adding 3% molasses can produce the highest-quality avocado seed meal silage as an optimal feed for livestock.